Significance of the modular approach for independent work of students when studying grammar of a foreign language at non-language university - Yuliya S. Elagina; Kseniya S. Oparina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In recent decades, through the introduction of a degree structure in higher education, Russia is highly integrated into the world socio-economic, information, educational and cultural space.Increased interaction with foreign partners implies that young professionals have sufficiently high level of knowledge of foreign languages. Increasing attention is therefore being paid to the development of graduates of the foreign language communicative competence in technical universities. An important condition for the successful study of a foreign language is a competent organization of independent work of students. The purpose of this study is to determine the effectiveness of a modular approach in the organization of independent work of students during the process of their study of a foreign language, in particular, grammar, at a technical university. The authors of this article consider the modular approach as a technology in which the content is divided into several units or modules, each of which is studied separately. The study is based on qualitative and quantitative methods, as well as an experiment in teaching. Educating process of students was conducted with the help of manuals of English grammar, published at the Department of Linguistics, Intercultural Communication and Russian as a Foreign Language of SamSTU and the Department of Theory and Practice of Translation of OSU. The experiment showed that the use of the modular approach applied to the study of English grammar in the framework of independent work of students was more effective than traditional methods. Moreover, the students noted that this teaching technology had clearly showed them the existing knowledge gaps and increased their motivation for their further study of grammar. The teachers in their turn appreciated the opportunity to adapt the content of classes depending on the individual level of each student, providing more flexible approach in the process of learning the English language.